The Influence of Organizational Culture and Work Environment on the Performance of Start-Up Companies in Yogyakarta - Dodi Setiawan Riatmaja; Sigit Wibawanto (Fokus Bisnis : Media Pengkajian Manajemen dan Akuntansi, 2021)
The purpose of this study was to determine the effect of Organizational Culture, work environment on employee job satisfaction, to determine the effect of Organizational Culture, Work Environment on Employee Performance; to determine the effect of job satisfaction on employee performance; knowing the role of job satisfaction as a mediator of organizational culture, and work environment in influencing employee performance at PT Mataram Surya Visi Yogyakarta. This research was conducted by taking from Mataram Surya Visi Yogyakarta employees as many as 73 employees. The calculation technique used in this study is the Multiple Linear Regression Analysis model and path analysis. Based on the analysis results indicate that there is a significant influence between organizational culture on job satisfaction; there is a significant influence between the work environment on job satisfaction; there is a significant influence between organizational culture and work environment on employee job satisfaction; there is a significant influence between organizational culture on performance; there is a significant influence between the work environment on performance; there is a significant influence between organizational culture and work environment on employee performance; there is a significant effect between satisfaction on performance; organizational culture indirectly on employee performance through job satisfaction and work environment indirectly on employee performance through job satisfaction.